Postgraduate Course as a Level of Higher Education: Status, Problems, Possible Solutions - Evgeniya V. Karavaeva; Vladimir V. Malandin; Irina A. Mosicheva; Irina G. Teleshova (Высшее образование в России)
The article analyzes the features of the “new” postgraduate course programs that have been implemented in the system of higher education in Russia since 2013. The article also identifies and describes the most vulnerable areas of the “new” postgraduate course and looks at solutions to the identified issues. The analysis of the features and the classification of the problems related to the implementation of doctoral studies as the third level of higher education are based on the results of analytical and sociological researches conducted in Lomonosov Moscow State University, Moscow Pedagogical State University, Association of the Classical Universities in Russia in 2017–2018. When formulating their recommendations on overcoming the challenges facing “new” doctoral education, the authors took into consideration the draft law “About scientific, technical, and innovation activities”, the key priorities of the National project “Science”, and the approaches to the creation of a new qualification system of scientific, research and pedagogical personnel.